2010
DOI: 10.1038/nm.2238
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hepatitis C virus particle formation requires diacylglycerol acyltransferase-1

Abstract: Hepatitis C virus (HCV) infection is closely tied to the lipid metabolism of liver cells. Here, we identify the triglyceride-synthesizing enzyme DGAT1 as an important host factor for HCV infection; DGAT1 interacts with the viral nucleocapsid core and is required for the trafficking of core to lipid droplets. Inhibition of DGAT1 activity or RNAi-mediated knockdown severely impairs infectious virion production, implicating DGAT1 as a new target for antiviral therapy.Over 160 million individuals are infected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
302
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 312 publications
(311 citation statements)
references
References 20 publications
6
302
1
2
Order By: Relevance
“…mDGAT1 point mutants and small hairpin RNA vectors targeting DGAT1 and DGAT2 were also generated as described (11). Luc-Jc1 reporter virus was described (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…mDGAT1 point mutants and small hairpin RNA vectors targeting DGAT1 and DGAT2 were also generated as described (11). Luc-Jc1 reporter virus was described (14).…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that the HCV core protein interacts with DGAT1 and depends on DGAT1 activity for access to LDs. Inhibition of DGAT1 activity or RNAi-mediated knockdown of DGAT1 severely impaired HCV infectious particle production, demonstrating DGAT1 is critical to HCV infection (11,12).…”
mentioning
confidence: 99%
“…155 NS5A is also targeted to the surface of LDs and presumably via a core-NS5A interaction the early step of assembly is triggered. 59 Indeed, point mutations interfering with core-NS5A co-localization at LDs strongly impair virus production.…”
Section: Discussionmentioning
confidence: 99%
“…The structural formula of inhibitor compound A (iA) is 2-((1s,4s)-4-(4-(4-amino-7,7-dimethyl-7H-pyrimido [4,5-b] [1,4]oxazin-6-yl)phenyl)cyclohexyl)acetic acid, and its use as a DGAT1 inhibitor has been described in Ref. 22 …”
Section: Methodsmentioning
confidence: 99%